Integration Analysis of JAK2 or RUNX1 Mutation With Bone Marrow Blast Can Improve Risk Stratification in the Patients With Lower Risk Myelodysplastic Syndrome - Fang, Ying; Guo, Juan; Wu, Dong; Wu, Ling-Yun; Song, Lu-Xi; Zhang, Zheng; Zhao, You-Shan; Chang, Chun-Kang (Frontiers in Oncology, 2021)
Despite the improvements in prognostication of the revised International Prognostic Scoring System (IPSS-R) in myelodysplastic syndrome (MDS), there remain a portion of patients with lower risk (low/intermediate risk, LR) but poor prognostics. This study aimed to evaluate the relative contribution of mutational status when added to the IPSS-R, for estimating overall survival (OS) and progression-free survival (PFS) in patients with LR-MDS. We retrospectively analyzed clinical and laboratory variables of 328 patients diagnosed with MDS according to the FAB criteria. 29-gene NGS assay was applied to bone marrow samples obtained at diagnosis. 233 (71.04%) patients were classified as LR-MDS. Univariate analysis showed association between inferior outcome (OS and PFS) and presence of JAK2 (p=0.0177, p=0.0002), RUNX1 (p=0.0250, p=0.0387) and U2AF1 (p=0.0227, p=0.7995) mutations. Multivariable survival analysis revealed JAK2 (p<0.0001) and RUNX1 (p=0.0215) mutations were independently prognostic for PFS in LR-MDS. Interestingly, bone marrow blast >1.5% could further predict disease progression of patients with LR-MDS [HR 8.06, 95%CI 2.95-22.04, p<0.0001]. Incorporation of JAK2, RUNX1 mutation and bone marrow blast in the IPSS-R can improve risk stratification in patients with LR-MDS. In summary, our result provided new risk factors for LR-MDS prognostics to identify candidates for early therapeutic intervention.